1984
DOI: 10.1093/ee/13.6.1459
|View full text |Cite
|
Sign up to set email alerts
|

Errors Incurred When Using Iwao's Sequential Decision Rule in Insect Sampling

Abstract: Sequential decision rules based upon defining a relationship between the mean and variance of a population and using this relationship in a confidence interval about a sum of counts on sample units have been developed and used for sampling insect pests. The actual error rates that arise from the use of these rules are much larger than the nominal ones. This occurs for three reasons: The confidence interval is incorrectly used as a sequential decision rule; it is assumed that random variables are normally distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

1985
1985
2009
2009

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 5 publications
0
25
0
1
Order By: Relevance
“…Consequently, the OC function underestimates the ␣ near 2 and overestimates ␤ near 1 (Fowler 1978, Fowler andLynch 1987). Thus, it is suggested that ␣ and ␤ be used as parameters that can be adjusted to provide acceptable OC and ASN functions and that this makes the cost/reliability trade-off a vital part of the sampling program (Nyrop and Simmons 1984, Nyrop et al 1989, Nyrop and Binns 1990. Considering these issues and with adjustments to the sampling plan parameters, the resulting OC functions of each sampling plan under consideration can be used to generate a decision probability analysis and determine the best sampling plan (Tables 1Ð3).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the OC function underestimates the ␣ near 2 and overestimates ␤ near 1 (Fowler 1978, Fowler andLynch 1987). Thus, it is suggested that ␣ and ␤ be used as parameters that can be adjusted to provide acceptable OC and ASN functions and that this makes the cost/reliability trade-off a vital part of the sampling program (Nyrop and Simmons 1984, Nyrop et al 1989, Nyrop and Binns 1990. Considering these issues and with adjustments to the sampling plan parameters, the resulting OC functions of each sampling plan under consideration can be used to generate a decision probability analysis and determine the best sampling plan (Tables 1Ð3).…”
Section: Discussionmentioning
confidence: 99%
“…A decision on whether to spray could readily be reached for 8-10 fields in 1 day, depending on distance between fields. This level of sampling has a 25% probability of yielding an incorrect population assessment, which represents a higher frequency of sequential decision errors than sampling programs at the two higher precision levels (Nyrop and Simmons 1984), a .40% likelihood of having to resample, and a 13% possibility of making an incorrect control decision in fields. The latter two assessments, though, were from fields that were selected because the probability of their larval populations being near or above economic thresholds was higher.…”
Section: Discussionmentioning
confidence: 99%
“…Both the operating characteristics and the average sample size are affected by the statistical assumptions of the particular method chosen. Of particular importance is the assumption that the precision level is fixed, which is not usually valid (Nyrop and Simmons 1984). This assumption is less critical for sweep sampling than for counts on individual plants because the sampling unit consists of many sweeps and the counts are essentially means.…”
Section: Discussionmentioning
confidence: 99%